Engaging Students Through PowerPoint: The Power of Multimodal Learning - Dewi M, Cantika Sari; Pratiwi, Dwiyani; Yulia, Yuyun (VELES Voices of English Language Education Society, 2024)
Teachers play a crucial role in fostering a positive and motivating learning environment for their students. One effective method to enhance student learning motivation is the use of PowerPoint as a multimodal tool. This study aimed to enhance students' learning motivation using PowerPoint in this capacity. Classroom Action Research (CAR) was applied, with 36 XI-grade hospitality students selected through purposive sampling. Field notes were used to record the implementation process, observation sheets examined improvements in students' learning motivation, and interviews identified the challenges of using PowerPoint as a multimodal tool. The results demonstrated that using PowerPoint effectively enhanced student learning motivation, with student participation increasing from 49.2% in the preliminary study to 77.7% after the intervention. Significant improvements were observed in various aspects: attentiveness, expression of ideas, task completion, active participation, collaboration, and engagement in group discussions. However, the study also highlighted challenges, such as the need for expertise in seamlessly integrating PowerPoint and tailoring materials to diverse student needs, including facility-related issues. These findings suggest the necessity for future research to investigate teacher training programs and examine the impact of various multimodal elements in PowerPoint presentations on student engagement. Despite the challenges, PowerPoint remains a promising tool for enhancing classroom dynamics and student motivation.